A retrospective study of Reyanning mixture in elderly patients infected with SARS-CoV-2 Omicron variant - Liu, Changya; Wu, Xinxin; Yang, Hongqiang; Xu, Xiangru; Chen, Caiyu; Wu, Linguangjin; Zhang, Wen; Shi, Haimei; Fei, Yuerong; Sun, Yuting; Wu, Hongze; Zhou, Shuang; et al. (Frontiers in Pharmacology, 2023)
Abstract Objective: Reyanning mixture has been demonstrated to be effective in treating infected patients during the outbreak pandemic of SARS-CoV-2 Omicron variant of Coronavirus disease 2019 (COVID-19) in Shanghai 2022. The aim of this study is to further investigate the role of Reyanning mixture specifically in the treatment of elderly patients. Methods: This study enrolled 1102 elderly patients who were infected with SARS-CoV-2 Omicron variant. Of these, 291 patients received Reyanning mixture in conjunction with conventional Western medicine treatment were assigned to the treatment group, while 811 patients only received conventional Western medicine treatment were assigned to the control group. Clinical parameters including hospitalization duration, viral shedding time, and Cycle Threshold (Ct) values of novel coronavirus nucleic acid tests, as well as adverse events were recorded and analyzed in both groups. Results: There was no significant difference in baseline characteristics between two groups. In comparison to the control group, the treatment group demonstrated a substantial difference in hospitalization duration (median: 8 d vs. 10 d, HR: 0.638, 95% CI: 0.558-0.731, p < 0.001). The treatment group also showed a significantly shorter viral shedding time compared to the control group (median: 7 d vs. 8 d, HR: 0.754, 95% CI: 0.659-0.863, p < 0.001). Multivariate Cox proportional-hazards model analysis indicated that the use of Reyanning mixture was closely associated with a reduction in hospitalization duration (HR: 1.562, 95% CI: 1.364–1.789, p < 0.001) and viral shedding time (HR: 1.335, 95% CI: 1.166–1.528, p < 0.001). In addition, during the treatment process, no serious adverse event occurred in either group. Conclusion: The improvement of clinical parameters in the treatment group indicate a promising therapeutic benefit of Reyanning mixture for elderly patients infected with SARS-CoV-2 Omicron variant in the present study. Further investigations are required to validate this finding by examining the underlying mechanism and function of Reyanning mixture.